Technologies of cryoprotectant‐free vitrification of human spermatozoa: asepticity as criterion of effectiveness. (9th October 2017) - Isachenko, V.; Rahimi, G.; Mallmann, P.; Sanchez, R.; Isachenko, E.
Summary: This review describes 120 years history of technology for cryoprotectant‐free cryopreservation of human spermatozoa by direct plunging into liquid nitrogen (vitrification). It is presented an explanation why cryoprotectant‐free vitrification for some human ejaculates is better than conventional freezing and vitrification with the presence of cryoprotectants. Special attention is given to the extremely high viability of viruses, bacteria and micoplasmas after cryoprotectant‐free cryopreservation in culture medium and even in distilled water. This fact increases the potential risk of disease transmission through liquid nitrogen. It is concretized the concept "asepticity" as obvious parameter for any medical assisted reproduction technology which includes the cooling of cells in liquid nitrogen. It is described the role of nonpermeable compounds of mediums for cryoprotectant‐free vitrification: carbohydrates, proteins, lipoproteins, antioxidants. This review summarizes concerned data regarding two groups of different current technologies for cryoprotectant‐free vitrification of human spermatozoa: with direct contact of spermatozoa with liquid nitrogen as well as with full isolation of these cells from liquid nitrogen (aseptic technologies).